2012
DOI: 10.33073/pjm-2012-044
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Helicobacter pylori Infection and Biliary Tract Diseases

Abstract: There are ambiguous results about the involvement of Helicobacter species in production of hepatobiliary diseases. This study was aimed to investigate any possible association between the presences of Helicobacter spp., their genotypes and occurrence of different biliary diseases. Cultures of 102 bile samples for Helicobacter spp. did not show any growth, but the presence of Helicobacter genus specific DNA (16s rRNA gene) was detected in 3.92% of them. No significant association was found between development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…did not show any growth, but the presence of Helicobacter pylori DNA by PCR was detected in 3.92% of them. No significant association was found between the development of the diseases and presence of the bacteria [75].…”
Section: Helicobacter Pylori and Helicobacter Spp In Bile Gallbladder Tissue And Gallstonesmentioning
confidence: 79%
See 2 more Smart Citations
“…did not show any growth, but the presence of Helicobacter pylori DNA by PCR was detected in 3.92% of them. No significant association was found between the development of the diseases and presence of the bacteria [75].…”
Section: Helicobacter Pylori and Helicobacter Spp In Bile Gallbladder Tissue And Gallstonesmentioning
confidence: 79%
“…Helicobacter spp. and Helicobacter pylori in bile samples, gallbladder tissue, and gallstones were detected by several methods: using cultures [52,59,67,71], by immunohistochemistry [46], by urease test, Giemsa, and immunohistochemical stain [72], by 16S rRNA PCR-amplification, by nested and multiplex PCR [47,[54][55][56][59][60][61][62][63][64]67,71,[73][74][75][76][77], by PCR-DGGE [52], both by PCR and by an ELISA study of the specific antigen (H. pylori stool antigen) [47], by ELISA after a preabsorption step using H. pylori antigens [46,78], by a Western blot analysis of Helicobacter antibodies [67], or by WMS sequencing and 16S rRNA sequencing on bile samples [35].…”
Section: Helicobacter Pylori and Helicobacter Spp In Bile Gallbladder Tissue And Gallstonesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies conducted so far showed a high variability in methods and also in findings. In some studies a strong association between H. pylori and biliary tract diseases was reported, while others failed to find a statistically significant association [28-30]. Furthermore, some studies have examined the link between H. pylori infection and cholecystitis, gallbladder cancer, but results have been inconsistent [31-43].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, more and more studies reported the existence of H. pylori in the bile, tissue, and stones of patients with chronic cholecystitis/cholelithiasis and tried to explain the relationship between them . It is a pity that it did not confirm any association between H. pylori infection and cholesterol gallstone formation in a mice study .…”
Section: Introductionmentioning
confidence: 99%